Perkembangan Pengembangan Badan Usaha Milik Desa Dalam Sektor Pertanian sebagai upaya Peningkatan Ketahan Pangan Desa Prasung - wiwin yulianingsih (Faculty of Law, 2020)
Prasung village located in Sidoarjo Regency is flanked by two rivers, Porong and Kali Mas, so it has fertile agricultural land that is can be a mainstay as a center for food security. So that a breakthrough in the management of development in the agricultural sector is needed through the establishment of the Village Owned Enterprises (BUMDes) of Agriculture that will manage agricultural products in order to provide great benefits to the people of Prasung Village in improving the economy, welfare and can improve food security. The need for community empowerment in managing the results of their fields through the BUMDes Agriculture that can also open jobs for the surrounding community. BUMDes Agriculture which will be developed in addition to being intended to increase the village's original income also has a social function. This community service activity is carried out with the method of socialization by providing understanding to the community in an effort to increase the potential in the village to support the welfare of the local community through the development of the Agricultural BUMDes in the Village of Prasung. The embodiment of the establishment of the BUMDes Agriculture is expected to minimize the role of middlemen, which often leads to increasing transaction costs between the price of products from producers to consumers. So that this BUMDes Agriculture can later help the community in the production of food for the consumption of local village community food. BUMDes in later can become a distributor that fosters economic activities in the local village so that of course requires a strong foundation in its development.